Giant Pseudoaneurysm as a delayed Surgical Complication in a Patient Operated on a Giant Neuroma of the Vagus Nerve: Case Report and Management Considerations - Manzano-Lopez, Demian; Rubino, Pablo; Teran, Pablo Mendivil; Baraza, Jesús Lafuente; Bertran, Gerardo Conesa (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
The vertebral artery has four segments. The horizontal portion of the V3 segment is the most exposed portion of the vertebral artery to potential iatrogenic injuries during surgical approaches to the posterior fossa. We present an unusual case of a patient who was operated on a giant neuroma of the left vagus nerve, with incidental vertebral artery iatrogenic injury, the development of a delayed giant pseudoaneurysm, and the treatment for this complication. We conclude that endovascular treatment may be a good option for the management of this serious surgical complication.
Keywords: posterior fossa approach; pseudoaneurysm; vertebral artery; endovascular treatement